Efeito da infecção pelo vírus da febre amarela no mecanismo de splicing celular - Ribeiro, Milene Rocha [UNESP] (2014)
Yellow fever virus (YFV) causes disease with significant morbidity and mortality in tropical regions. Several viral strategies are avail for recruitment and alteration of the biochemical cellular processes. Cellular splicing mechanisms are essential to diversify the gene expression and increase it’s proteomic potential. Replication of YFV and the interactions between viral and cellular proteins are unknown. The cellular protein hSlu7 has an nuclear localization and an important role in the second catalytic reaction step of the alternative splicing. In our study group demonstrated that under YFV infection hSlu7 translocates to the cytoplasm. The translocation of proteins between nucleus and cytoplasm may represent a viral mechanism of cellular gene expression regulation, interference in the protein availability of the alternative splicing and viral replication control. This study aimed to characterize the interaction between the viral protein hSlu7 and NS5, as well as studying the effects of interactions on the mechanisms of alternative splicing after YFV infection. To identify interaction with YFV NS5 hSlu7 was conducted co-immunoprecipitation assay. To verify changes in cellular splicing replicons were used pEGFP-ADAR, PI12-IL7R, pEFGP-FGFR2 as well as the change of isoforms of XBP-1 endogenous.The results indicated that YFV NS5 protein interacts with hSlu7 and that their interaction may influence cellular metabolism RNA. YFV perform modulation on cellular splicing, the evaluation of replicons suggest that in hSlu7 splicing dependent and independent regulation occurs viral acting on weak splice sites and that the interaction hSlu7-NS5 can change directly or indirectly to regulate trans- acting